(untitled) (Microbes and Health, 2016)
Sulfate-reducing bacteria produce hydrogen sulfide which is toxic and carcinogenic for intestinal epithelial cells and can cause the development of the inflammatory bowel disease and ulcerative colitis in the humans and animals. Enzyme O-acetylserine(thiol)lyase, localized in Escherichia coli genome, use sulfide as substrate in the cysteine synthesis pathway. In this paper, the molecular cloning cysK gene from E. coli, its genetic transferring in the intestinal sulfate-reducing bacterium Desulfovibrio piger Vib-7 and the expression analysis of the enzyme was studied. Cysteine synthesis from hydrogen sulfide as substrate in the D. piger Vib-7 strain at the first time was demonstrated and characterized. The bacterial growth, sulfate and lactate consumption, accumulation of sulfide, acetate and cysteine synthesis in both D. piger Vib-7 wild-type and mutant-type were tested. The mutant-strain consumed much faster sulfate and lactate producing cysteine in the cultivation medium. The expression of the cysK gene in the mutant-type was studied by the formation of the final reaction product (cysteine) and the activity of O-acetylserine(thiol)lyase enzyme. Cysteine level was directly proportional to consumption of sulfate in the mutant-type and accumulation of sulfide in the wild-type. The D. piger Vib-7 mutant-type completely used sulfate the 48th hour of cultivation, thereafter additional sulfite and sulfide doses from the medium were also consumed and converted to cysteine. The obtained genetically constructed mutant strain bacterium D. piger Vib-7 for therapeutic strategy could be applied as a probiotic substance for subjects with inflammatory bowel disease and ulcerative colitis. This strain can compete with other intestinal sulfate-reducing bacteria, actively growth consuming sulfate and lactate much faster, and converting the toxic sulfide to untoxic cysteine in the gut. Microbes and Health, January 2015. 4(1): 19-24